2005
DOI: 10.1080/08916930400022699
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ribosomal P protein antibodies

Abstract: Anti-ribosomal P protein antibodies (Abs) recognize three specific ribosomal proteins located in the large ribosome's subunit. The term anti-ribosomal P protein Abs, often shortened in anti-P Abs, is due to the fact that these three proteins, P0, P1 and P2, of 38, 19 and 17 Kd molecular weight, respectively, are phosphorylated. One of the major points of interest of these autoAbs derives from their high specificity for systemic lupus erythematosus (SLE), their description in other connective tissue diseases (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 10 publications
3
57
2
Order By: Relevance
“…Several studies have shown that both the acidic and hydrophobic clusters, but not the phosphorylation of the P proteins, are critical for autoantibody binding (8,16,23). Furthermore, epitope mapping studies have shown that the major epitope domain is located within the last six C-terminal amino acids (GFGLFD) (8,16,23).The reported prevalence of anti-Rib-P antibodies in SLE ranges from 10 to 40%, being higher in Asian patients and at a relatively lower prevalence in black and Caucasian patients (3,12,15,18,23,30,35). The variation in the observed frequency may be related to a number of factors but is dependent in large part on the test system used to detect the autoantibodies.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that both the acidic and hydrophobic clusters, but not the phosphorylation of the P proteins, are critical for autoantibody binding (8,16,23). Furthermore, epitope mapping studies have shown that the major epitope domain is located within the last six C-terminal amino acids (GFGLFD) (8,16,23).The reported prevalence of anti-Rib-P antibodies in SLE ranges from 10 to 40%, being higher in Asian patients and at a relatively lower prevalence in black and Caucasian patients (3,12,15,18,23,30,35). The variation in the observed frequency may be related to a number of factors but is dependent in large part on the test system used to detect the autoantibodies.…”
mentioning
confidence: 99%
“…Anti-Rib-P antibodies were mainly detected in patients during the active phase of SLE and were believed to be correlated with lupus nephritis or hepatitis (4,11,12,24,28,30,36).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies, however, did not confirm these observations and this relationship is still a matter of debate [2,3,11,12]. Anti-P antibodies were also related to renal involvement in SLE patients such as anti-dsDNA [13,14].…”
Section: Discussionmentioning
confidence: 83%